2022
DOI: 10.3390/jof8030263
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing of Wound Healing in Burn Patients through Candida albicans β-Glucan

Abstract: The mortality and disability-adjusted life years (DALYs) of burn patients are decreasing over time. However, finding novel effective treatment approaches using natural agents is highly considered to reduce the burden of burn injuries. One of the recent agents used in wound healing is β-glucan, mainly extracted from fungi cell walls. This study aimed to evaluate the effect of 5% (m/m) of yeast β-glucan ointment on burn wound healing and to assess the impact of β-glucan on cytokines during the treatment. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The evaluation results showed that patients who received β-glucan ointment showed better wound healing (RR = 4.34; 95% Cl; 0.73 to 25.67; p = 0.11). In addition, patients receiving β-glucan ointment showed a significant difference in the level of IL-4 cytokine secretion compared to the control group ( Abedini et al, 2022 ). According to these results, β-glucan can be mentioned as an ideal natural biopolymer in wound healing applications.…”
Section: Biomaterials Used In Wound Healingmentioning
confidence: 98%
“…The evaluation results showed that patients who received β-glucan ointment showed better wound healing (RR = 4.34; 95% Cl; 0.73 to 25.67; p = 0.11). In addition, patients receiving β-glucan ointment showed a significant difference in the level of IL-4 cytokine secretion compared to the control group ( Abedini et al, 2022 ). According to these results, β-glucan can be mentioned as an ideal natural biopolymer in wound healing applications.…”
Section: Biomaterials Used In Wound Healingmentioning
confidence: 98%
“…Due to an imbalance between inflammatory cells and inhibitors, chronic wounds usually stagnate in the inflammatory phase ( Schultz, et al, 2003 ; Satish, 2015 ). Overexpression of interferon-gamma (IFN-γ), a proinflammatory cytokine that is essential for the regulation of collagen synthesis, delays wound healing, and dysfunction of interleukin-17 (IL-17) inhibits progression to the proliferation phase in nonhealing wounds ( Abedini, et al, 2022 ). Compared with acute wounds, nonhealing wounds display clinical, morphological, microbiological and biochemical differences ( Kirker, et al, 2017 ).…”
Section: Wound Healing Process and Impaired Healing In Chronic Woundsmentioning
confidence: 99%
“…Multiple features of β-glucan, including anticancer (14), anti-diabetic (15), anti-inflammatory, and a decrease in the glycemic index as well as serum cholesterol and triglycerides, have been demonstrated. β-glucans maintain the balance of blood glucose and cardiovascular diseases (16), enhance the immune system (17) and wound healing activities (18), and show antimicrobial (antibacterial and antiviral) properties (Figure 1). Proved antioxidant, wound healing, and moisturizing properties of β-glucan derived from microorganisms and cereal (19).…”
Section: Introductionmentioning
confidence: 99%